Extraction of Natural Dyes from Cocoa Pod Husk (Theobroma cacao L.) using Ultrasound Assisted Extraction as a Natural Fabric Dye - Utami, Herti; Harahap, Katrina; Pista, Annisa Fitria; Azizah, Ara Annastasya; Marlina, Arlin; Darni, Yuli; Ginting, Simparmin br (Jurnal Rekayasa Kimia & Lingkungan, 2024)
Natural dyes are one of the popular choices for textile dyes today. One part of the plant that has the potential to produce natural dyes is cocoa pod husk (Theobroma cacao L.) because it contains several secondary metabolite compounds, such as tannin which produces a brown color. The extraction method used in this research is Ultrasonic Assisted Extraction (UAE). This study aims to obtain the highest yield of natural dye extracts from cocoa pod husk by varying solvent types, extraction time, and material-to-solvent ratios using the UAE method. In addition, the types of compounds contained in extracts of natural dyes and color results on cotton fabrics were also obtained. The extraction process was carried out using several types of solvents, namely methanol, ethanol, acetone, and distilled water with varying extraction times of 30, 60, and 90 minutes. The research results show that the solvent that can extract the best natural dyes was ethanol with a yield of 11.43% and an extraction time of 90 minutes. Variable ratios of material to 96% ethanol solvent were also observed, namely at ratios of 1:5, 1:6, 1:7, and 1:8 for extraction times of 30, 60, 90, and 120 minutes. The research results were obtained for the ratio of material to ethanol solvent; 1:8 (w/v) and extraction time 120 minutes with a dye yield of 12.29%. The results of the UV-visible spectrophotometry analysis were obtained that the maximum wavelength of cocoa pod husk extract was 656.5 nm with an absorbance of 0.532. The results of the Gas Chromatography-Mass Spectrometry (GC-MS) analysis were obtained that the dye compound in the cocoa pod husk was tannin. Tannin compounds are natural dyes that can be applied to fabrics and will reduce the use of synthetic dyes. The application of dye extracts to cotton fabrics produced a brown color.